2013
DOI: 10.1371/journal.pone.0072727
|View full text |Cite
|
Sign up to set email alerts
|

What Are You or Who Are You? The Emergence of Social Interaction between Dog and an Unidentified Moving Object (UMO)

Abstract: Robots offer new possibilities for investigating animal social behaviour. This method enhances controllability and reproducibility of experimental techniques, and it allows also the experimental separation of the effects of bodily appearance (embodiment) and behaviour. In the present study we examined dogs’ interactive behaviour in a problem solving task (in which the dog has no access to the food) with three different social partners, two of which were robots and the third a human behaving in a robot-like man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 32 publications
3
51
0
Order By: Relevance
“…In summary, we propose that the observed flexibility of dogs' social behaviour is due to sharing an environment with humans (heterospecific agents); thus they are probably able to generalize their wide range of social experience with humans to another type of agent as well. These results support the findings that dogs are able to attend to some social aspect of the behaviour of a UMO which resembles neither conspecifics nor humans (Gergely et al, 2013). The relatively little experience with the UMO suggests that it is unlikely that the present results can be explained solely on the basis of ontogenetic processes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In summary, we propose that the observed flexibility of dogs' social behaviour is due to sharing an environment with humans (heterospecific agents); thus they are probably able to generalize their wide range of social experience with humans to another type of agent as well. These results support the findings that dogs are able to attend to some social aspect of the behaviour of a UMO which resembles neither conspecifics nor humans (Gergely et al, 2013). The relatively little experience with the UMO suggests that it is unlikely that the present results can be explained solely on the basis of ontogenetic processes.…”
Section: Discussionsupporting
confidence: 88%
“…In the Interactive Human and Noninteractive Human conditions the partner was an unfamiliar female human (see Gergely, Petr o, Top al, & Mikl osi, 2013). During the familiarization phase, dogs in the Interactive UMO and Human conditions were presented with a problem situation (Context 1) in which the UMO or a human helped the dog to get an unreachable food reward (see Gergely et al, 2013;Mikl osi, Polg ardi, Top al, & Cs anyi, 2000). In contrast, no such interaction took place in the Noninteractive conditions.…”
mentioning
confidence: 99%
“…Several studies with domestic dogs support this assumption (Szetei et al, 2003; Erdõhegyi et al, 2007; and see also Topál et al, 2009) in which researchers showed that some aspect of dogs’ cognitive skills can be masked by using human social communicative cues and thus false conclusions can be drawn about their cognitive abilities. Utilization of unfamiliar moving inanimate objects (robots) as social partners can be useful in such investigations especially if the physical appearance of the robot does not resemble the embodiment of the subject species or any heterospecifics with whom they engage in daily interactions (Gergely et al, 2013). This way the test itself can be controlled by the experimenter more efficiently and it is also less likely that the robotic partner induces aversion.…”
Section: Discussionmentioning
confidence: 99%
“…Gergely et al, 2015), this does not necessarily entail that dogs attribute agency because they recognized the contingent reactivity of an unfamiliar agent. They might simply use other agency cues, such as goal directedness (G. Gergely & Csibra, 2003) or differences in the variability of motion (A. Gergely, Petró, Topál, & Miklósi, 2013). Thus, it remains unknown whether dogs are sensitive to the role that temporal contingency plays in interactions among agents and whether they can attribute agency on the basis of the observed contingent reactivity.…”
mentioning
confidence: 99%